(untitled) (Damascus University Journal of agriculture sciences, 2022)
These investigations were carried out in 2019-2020, at the Department of Plant Protection- Damascus University, the Faculty of Agriculture, Damascus University. In the present work, chemical composition of essential oil of Zattar (Thymus syriacus Boiss: Lamiaceae) from the mountain of Rural Damascus –Syria It was determined by Chromatography- Mass Spectrometry GC/MS. T. syriacus leaves at vegetative stage oil was isolated by hydrodistillation. The 11 components were identified in T. syriacus oil and the main components were as follows; (9.32%), Thymol (42.30%), and Carvacrol (8.70%). In Addition, this study investigated the potential of ethanol extract of T. syriacus leaves to control the olive fruit fly. Freshly emerged female and male adults of Bactrocera oleae (Gmel) ( Diptera,Tephritidae (were continuously fed for 12 days on diet containing 125,250,500,750, 1000, 1250 and ppm of ethanol extract of T. syriacus leaves separately in laboratory cages. The extract caused 71.83, 80.08 and 93.85 % mortality at 1500 ppm after 3, 6 and 12 days of treatment, respectively. The surviving adults flies were mated and allowed to reproduce on clean olive fruits in separate cages. The inhibition in pupal progeny was 52.32, 68.85 and 73.49 % in the flies fed on 250, 500 and 1000 ppm, the inhibition observed in adult progeny was 69.33, 76.67 and 85.33%, respectively